Rotor position estimating scheme for doubly salient EM machine sensorless startup. Issue 15 (1st July 2017) - Zhou, Xingwei; Zhou, Bo
Abstract : A novel rotor position estimation method for doubly salient EM motor (DSEM) sensorless startup is proposed. On the basis of the feature the series self‐inductances of two energised phases are the greatest among all of the three two‐phase series self‐inductances under the basic conduction mode of DSEM, the voltage vector of next conduction state is selected as the test pulse which is injected for rotor position estimation. Moreover, the acceleration pulse, traditionally injected only for speedup, is newly proposed to be utilised for rotor position estimation. The rotor sector is obtained by comparing the two response currents, one of which is sampled at the end of test pulse, and the other is sampled when the acceleration pulse lasts to the duration of test pulse. Since only one test pulse is required, the sensorless startup performance of DSEM is improved in terms of less test time consuming, smaller estimation error as well as greater output torque. The experiments on a 12/8‐pole DSEM validate the correctness of the proposed rotor position estimation method.